2018
DOI: 10.1159/000493860
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction and Clinical Outcomes with Budesonide plus Formoterol Spiromax for Asthma and Chronic Obstructive Pulmonary Disease: A Real-World, Observational Trial

Abstract: Background: The fixed-dose combination of budesonide/formoterol (B/F) has been available in the Spiromax® dry powder inhaler since 2014. Objectives: To assess patient satisfaction, inhaler use errors, and disease control in patients with asthma or chronic obstructive pulmonary disease (COPD) treated with B/F Spiromax. Methods: This non-interventional, prospective, 12-week study enrolled consecutive asthma or COPD patients who had recently begun treatment with B/F Spiromax or were switched from another inhaled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…Consistent with previous research among HCPs and patients, this study among practicing GPs confirmed that maintaining device mastery is problematic [7,[45][46][47][48]. It can be argued that 100% of prescribers should be maintaining correct IT after training, however despite this, we have found that maintaining correct IT was more likely with the Spiromax Ò than with the Turbuhaler Ò .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Consistent with previous research among HCPs and patients, this study among practicing GPs confirmed that maintaining device mastery is problematic [7,[45][46][47][48]. It can be argued that 100% of prescribers should be maintaining correct IT after training, however despite this, we have found that maintaining correct IT was more likely with the Spiromax Ò than with the Turbuhaler Ò .…”
Section: Discussionsupporting
confidence: 90%
“…The presentation of these two devices was consistent with the way in which each of the two manufacturers supply their ''placebo'' inhalers. We believe that this does in fact mimic the sensations experienced by patients when using these medication-filled devices [45,[47][48][49], however do recognize that it may be a source of bias in this study. The presence of lactose in the Spiromax Ò does equate to a feedback mechanism associated with use of this device.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Currently, the combination of different treatment methods is preferred for the treatment of COPD [14]. The treatment for COPD includes the use of bronchodilators and anti-inflammatory drugs to relieve the symptoms of airway obstruction and inhibit airway inflammation [15]. Clinically, the commonly used drugs are inhaled corticosteroids, which effectively relieve the clinical symptoms of COPD patients.…”
Section: Discussionmentioning
confidence: 99%